2020
DOI: 10.1590/1518-8345.3097.3214
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices of grandmothers related to breastfeeding: a meta-synthesis

Abstract: Objective: Evaluate the knowledge, attitudes and practices of grandmothers that support or discourage the breastfeeding process. Method: This is a meta-synthesis based on the theoretical and methodological framework of meta-ethnography developed by Noblit and Hare. A critical evaluation of the articles was conducted using the consolidated criteria for reporting qualitative research (Coreq). Primary and secondary constructs derived from the results of nine articles were grouped into a new theory, leading to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
1
13
0
6
Order By: Relevance
“…The differences found could be due to various aspects. First, the maternal desire to abandon breastfeeding can be influenced by the social and cultural context in which the mother lives, considering that grandmothers are key figures in the support and intergenerational transmission of breastfeeding [30,[32][33][34]. Sometimes, the maternal choice to abandon breastfeeding is due to the lack of family and social support.…”
Section: Discussionmentioning
confidence: 99%
“…The differences found could be due to various aspects. First, the maternal desire to abandon breastfeeding can be influenced by the social and cultural context in which the mother lives, considering that grandmothers are key figures in the support and intergenerational transmission of breastfeeding [30,[32][33][34]. Sometimes, the maternal choice to abandon breastfeeding is due to the lack of family and social support.…”
Section: Discussionmentioning
confidence: 99%
“…The differences founded could be due to various aspects. First of all, the maternal desire to abandon breastfeeding can be influenced by the social and cultural context in which the mother lives, being grandmothers a key in the support and the intergenerational transmission of breastfeeding [28][29][30]. Sometimes, maternal desire is given by a lack of family and social support.…”
Section: Discussionmentioning
confidence: 99%
“…This fact contributed to the discontinuity of EBF and, in some situations, added to the context of IPV and contributed to early weaning. In this regard, meta-synthesis ( 9 ) who assessed the knowledge, attitudes and practices of grandmothers related to the support offered in the practice of BF showed that they are central figures and influence daughters or daughters-in-law to breastfeed, by offering support, at the same time that they can promote the discontinuity of the act breastfeeding through contrary opinions and inadequate information. Therefore, it is necessary to understand that the network, mediated by the interpersonal context, can both promote support, well-being and changes, as well as the disarticulation of the individual and his ongoing internal processes ( 6 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The SSN can be defined as the set of interpersonal and social relationships ( 7 ) , which can play both a protective and a risky role for individuals, depending on the context in which these relationships develop ( 8 ) . Consequently, the relationships established in the SSN are associated with the social, cultural, political and religious contexts that are integrated among the generations and, in this sense, directly interfere in the way breastfeeding occurs in the live of women ( 9 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation